The Effect of Investment Income and Underwriting Results on Company Value with Profitability as a Mediating Variable in General Insurance Companies in Indonesia in 2020-2024 - Pristiwanto Bani; Wahyu Purbo Santoso; Ruswiati Suryasaputra; Pustika Ayuning Puri (Green Publisher Indonesia, 2026)
The general insurance industry has a strategic role in the national financial system through its risk management and public fundraising functions. This study aims to analyze the influence of underwriting results and investment income on profitability and company value, as well as examine the role of profitability as a mediating variable in general insurance companies in Indonesia. This study uses a quantitative method with secondary data obtained from the annual financial statements of general insurance companies for the period 2020–2024. The research sample consisted of general insurance companies selected through purposive sampling techniques. The analysis technique used was panel data regression with data processing using EViews software. The results show that underwriting results have a positive and significant effect on profitability, while investment income does not have a significant effect on profitability. Simultaneously, underwriting results and investment income have a significant effect on profitability. Furthermore, underwriting results and profitability do not have a significant effect on the company's value, while investment income has a positive and significant effect on the company's value. The results of the mediation test showed that profitability did not mediate the effect of underwriting results or investment income on the company's value. These findings indicate that underwriting performance plays a more role in determining profitability, while investment income is more directly considered by the market in assessing the value of the company.